Injury prevention strategies of landing motion of jumping front kick to apply Free Style Poomsae of Taekwondo - Ryu, S. (Korean Journal of Sport Biomechanics, 2020)
Objective: The purpose of this study was to investigate the injury factors of Taekwondo jumping kick during landing phase according to the experience of injury and to suggest a stable landing movement applicable to free style Poomsae. Method: The participants were non-injury group (NG), n = 5, age: 20.5±0.9 years; height: 171.6±3.6 cm; body weight: 65.7±4.4 kg; career: 5.0±2.7 years. Injury group (IG), n = 9, age: 21.0±0.8 years; height: 170.9±4.6 cm; body weight: 67.1±7.0 kg; career: 8.6±5.0 years. The variables are impact force, loading rate, vertical stiffness, lower limb joint angle, stability, balance, and muscle activity in the landing phase. Results: NG was statistically larger than IG in the gluteus medius (p<.05). The impact force, loading rate and vertical stiffness decreased as the landing foot angle, the ROM of lower limb joint angle and COM displacement increased (p<.05). Conclusion: Based on the results, it means that the landing foot angle plays an important role in the impact reduction during landing phase. It is required the training to adjust the landing foot angle.